2010
DOI: 10.1007/s00246-010-9648-2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prenatal Diagnosis of Complex Congenital Heart Disease on Neonatal Outcomes

Abstract: Prenatal diagnosis of congenital heart disease (CHD) is increasingly common. However, the current impact of prenatal diagnosis on neonatal outcomes is unclear. Between January 2004 and January 2008, a retrospective chart review of infants who underwent surgical repair of CHD before discharge at our institution was conducted. Obstetric and perioperative variables were recorded. Of 439 neonates, 294 (67%) were diagnosed prenatally (PREdx). Infants with PREdx had a lower mean birth weight (3.0 ± 0.6 vs. 3.1 ± 0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
115
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(133 citation statements)
references
References 16 publications
12
115
3
Order By: Relevance
“…544,545 Prenatal diagnosis may also predict the need for emergent postnatal intervention such as balloon atrial septostomy for d-TGA, 546,547 atrial septoplasty for HLHS, 176,548,549 or pacing in CHB, 550 thus improving outcome by allowing more rapid stabilization of the postnatal circulation. Finally, although hospital length of stay has been unaffected by prenatal diagnosis in some settings, 544,551 others report earlier time to surgical intervention and reduced length of hospital stay in neonates diagnosed in utero with critical heart disease who undergo biventricular repair. 545 …”
Section: Impact On Morbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…544,545 Prenatal diagnosis may also predict the need for emergent postnatal intervention such as balloon atrial septostomy for d-TGA, 546,547 atrial septoplasty for HLHS, 176,548,549 or pacing in CHB, 550 thus improving outcome by allowing more rapid stabilization of the postnatal circulation. Finally, although hospital length of stay has been unaffected by prenatal diagnosis in some settings, 544,551 others report earlier time to surgical intervention and reduced length of hospital stay in neonates diagnosed in utero with critical heart disease who undergo biventricular repair. 545 …”
Section: Impact On Morbiditymentioning
confidence: 99%
“…564,565 These observations are juxtaposed to concerning data from recent studies that have identified a small but significant negative trend in gestational age at delivery in infants with single-ventricle defects when diagnosed prenatally. 544,551,566 Close communication between obstetric and cardiology services is essential in this setting because elective induction for fetuses with CHD before 39 weeks is not recommended unless there are patient-specific obstetric or logistic issues or fetus-specific concerns about well-being.…”
Section: Logistical Considerationsmentioning
confidence: 99%
“…Prenatal detection is therefore particularly important for these newborn infants. [4][5][6][7][8] Over the past decade, first-trimester nuchal translucency (NT) measurement has been used increasingly for prenatal detection of chromosomal abnormalities and has been associated with CCHDs in pregnancies with and without aneuploidy. [9][10][11][12] Although an enlarged NT has been associated with CCHDs (defined by either an NT measurement percentile for crownrump-length [CRL] or by a specific NT measurement in millimeters), [9][10][11]13 having an NT measurement of 3.5 mm is the most commonly applied cutoff at which fetal echocardiography is recommended, based on guidelines of the American College of Obstetricians and Gynecologists.…”
mentioning
confidence: 99%
“…High rates of prenatal diagnoses of congenital heart disease and the state-wide guideline mandating birth of neonates with antenatal diagnosis of heart defects in a co-located perinatal centre could be one of the reasons for this trend [28][29][30]. It has been postulated that efforts to improve prenatal diagnosis and delivery close to a Primary cause of death…”
Section: Discussionmentioning
confidence: 99%